Analysis of the Halal Ecosystem and Halal Literacy on the Development of Islamic Economic Halal Regulation - Robi Krisna; Mohammad Yusuf; Eka Putra (Proceeding of The International Conference on Business and Economics, 2023)
The purpose of this study is to determine the Halal Ecosystem and Halal Literacy in the development of Sharia Economic Halal Regulations. This study explains the halal ecosystem as a whole and what is included in the halal ecosystem. In addition, it also discusses halal literacy in Indonesia. Halal literacy is very important for all countries to learn to prepare people to face an ever-changing financial system. People will need a more economical understanding to actively participate in a global economy that tends to change. The data analysis method in this research uses qualitative-descriptive analysis. Qualitative research is carried out to build knowledge through understanding and discovery, so it is expected to reveal a variety of information that is thorough and full of meaning, but also does not reject quantitative information in the form of numbers. The results of this study are that the ecosystem needed in improving the halal industry refers to the supply, demand and enabler approaches. From the supply aspect, the existence of the Indonesian halal industry sector (food, tourism, fashion, medicine, media and renewable energy) has prepared various products that can be consumed by the public with a halal label. Government support provided, both as regulators, executors and evaluators, is needed as an enabler component in the halal industry ecosystem. Products from the halal industry itself are experiencing quite rapid development, the halal food and beverage sector, the financial sector, tourism, fashion, cosmetics and medicines, media and entertainment, as well as other sectors such as health care and education.